2016
DOI: 10.1021/acs.nanolett.6b01314
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Coupling in Gold Nanoparticles Supermolecules Revealed by Plasmon-Enhanced Ultralow Frequency Raman Spectroscopy

Abstract: Acoustic vibrations of assemblies of gold nanoparticles were investigated using ultralow frequency micro-Raman scattering and finite element simulations. When exciting the assemblies resonantly with the surface plasmon resonance of electromagnetically coupled nanoparticles, Raman spectra present an ultralow frequency band whose frequency lies below the lowest Raman active Lamb mode of single nanoparticles that was observed. This feature was ascribed to a Raman vibration mode of gold nanoparticle "supermolecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(110 citation statements)
references
References 50 publications
7
102
1
Order By: Relevance
“…The values of the stiffnesses depend on the exact nature of the contacts in the sample, which are sensitive to the details of the preparation conditions. Raman and Brillouin spectroscopy studies have also revealed the existence of different types of vibrational modes involving particle contact [45,46]. A microscopic analysis of the origin of our observed stiffnesses is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 82%
“…The values of the stiffnesses depend on the exact nature of the contacts in the sample, which are sensitive to the details of the preparation conditions. Raman and Brillouin spectroscopy studies have also revealed the existence of different types of vibrational modes involving particle contact [45,46]. A microscopic analysis of the origin of our observed stiffnesses is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 82%
“…On one hand, considering vibrations propagating in a solid with a sound velocity of few 10 3 m/s, confined acoustic‐like atomic vibrations in nm‐sized metallic NCs must belong to the THz range, as observed experimentally . On the other hand, oscillations of uncompressible NCs, composed of few 10 3 atoms and weakly bounded by ligand chains, are expected in the GHz range . Therefore, the dynamical coupling between the two types of oscillators is expected to be weak.…”
Section: Introductionmentioning
confidence: 88%
“…[3,4] On the other hand, oscillations of uncompressible NCs, composed of few 10 3 atoms and weakly bounded by ligand chains, are expected in the GHz range. [5,6] Therefore, the dynamical coupling between the two types of oscillators is expected to be weak.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrations detected in LFR region are generated by harmonic oscillations such as lattice phonons and localized intermolecular interactions such as Van der Waals interactions, π–π stacking, and hydrogen bonds . The LFR signal is sensitive to the vibrational modes associated with the material nanostructure and is therefore being used to characterize chiral purity of organic crystals and formulations, biomolecular assemblies, metal–organic frameworks, semiconductor superlattices, and halide perovskites . However, because of the intense Rayleigh scattering and instrumental limitations associated with blocking the exciting beam, observing LFR signatures has been considered difficult.…”
Section: Introductionmentioning
confidence: 99%
“…[11] The LFR signal is sensitive to the vibrational † Tal Ben Uliel and Laxman Gouda have contributed equally to this work. modes associated with the material nanostructure [12] and is therefore being used to characterize chiral purity of organic crystals and formulations, [13] biomolecular assemblies, [14] metal-organic frameworks, [15] semiconductor superlattices, [16] and halide perovskites. [17] However, because of the intense Rayleigh scattering and instrumental limitations associated with blocking the exciting beam, observing LFR signatures has been considered difficult.…”
Section: Introductionmentioning
confidence: 99%